SNiPA : an interactive, genetic variant-centered annotation browser - Arnold, Matthias; Raffler, Johannes; Pfeufer, Arne; Suhre, Karsten; Kastenmüller, Gabi (Bioinformatics, 2015)
Motivation: Linking genes and functional information to genetic variants identified by association studies remains difficult. Resources containing extensive genomic annotations are available but often not fully utilized due to heterogeneous data formats. To enhance their accessibility, we integrated many annotation datasets into a user-friendly webserver. Availability and implementation:  http://www.snipa.org/ Contact:  g.kastenmueller@helmholtz-muenchen.de Supplementary information:  Supplementary data are available at Bioinformatics online.